Developing a Model of Organizational Inclusion in Multicultural Environments:Evidence from Government Organizations in Kermanshah Province, Iran - Hooshmand, Javad; Nazari, Kamran; Feghhi Farahmand, Nasser (Journal of Foresight and Health Governance, 2026)
Growing cultural diversity within public organizations has made organizational inclusion a strategic necessity rather than a symbolic commitment. In multicultural settings, inclusion refers to the creation of a fair, participatory, and respectful environment in which employees from different cultural and social backgrounds can contribute fully, access opportunities equitably, and experience genuine belonging. Kermanshah Province in western Iran offers an important empirical setting for examining this issue because of its substantial ethnic and cultural diversity and the managerial challenges this diversity can create in government institutions. This developmental-applied study used an exploratory sequential mixed-methods design. In the qualitative phase, semi-structured interviews were conducted with 16 managers, specialists, and key employees from government organizations in Kermanshah Province. Interview data were analyzed through inductive thematic analysis following the approach of Braun and Clarke. In the quantitative phase, the emergent model was tested using a researcher-made questionnaire administered to 384 employees selected by stratified random sampling from a population of 71,500 government employees. Instrument reliability was supported by a Cronbach's alpha of 0.906, and the quantitative model was examined using confirmatory factor analysis and structural equation modeling. The final model comprised four overarching dimensions and twelve components. The first dimension, an organizational culture of diversity acceptance, included institutionalizing diversity acceptance, establishing an anti-discrimination system, strengthening psychological safety, and promoting intercultural convergence. The second dimension, inclusion-oriented leadership, included exemplary inclusive leadership, transparent and fair decision-making governance, institutional support for marginalized employees, and systematic management of cultural and generational conflicts. The third dimension, transparent technologies and processes, included organizational feedback and participation systems and transparent evaluation mechanisms. The fourth dimension, training and skill development, included intercultural training and development and equality in access to resources and information. Qualitative coding yielded 295 initial codes, which were refined into 53 basic themes, 12 organizing themes, and 4 overarching themes. In the quantitative phase, all factor loadings exceeded 0.50. The highest second-order loading was observed for training and skill development (0.80), followed closely by organizational culture of diversity acceptance (0.79), while inclusion-oriented leadership and transparent technologies and processes showed loadings of 0.64 and 0.62, respectively. The proposed model demonstrated acceptable fit and can serve as a practical framework for strengthening organizational inclusion in multicultural public-sector environments. The findings suggest that inclusion in government organizations is most effectively advanced when cultural acceptance, inclusive leadership, transparent procedures, and equitable learning opportunities are addressed as mutually reinforcing organizational conditions.